EXPLORING INCLUSIVE PRACTICES ADDRESSING THE NEEDS OF MARGINALIZED LEARNERS TO ENRICH ACADEMIC ENVIRONMENTS IN FOSTERING HOLISTIC EDUCATION AT THE TERTIARY LEVEL - Shekhar, G. Raja; Gundala, Mr. Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The intensifying diversification of contemporary higher education has generated an urgent pedagogical and ethical imperative to reconceptualise inclusion beyond the reductive logic of accommodation and institutional tokenism. Universities increasingly engage with learners situated across multiple axes of marginalization, including socio-economic precarity, racial and ethnic exclusion, linguistic displacement, disability, neurodiversity, forced migration, and first-generation educational trajectories. Yet, despite the democratization of access, higher education institutions frequently continue to reproduce epistemic hierarchies, cultural hegemonies, and structurally exclusionary pedagogical practices that privilege dominant modes of knowledge production and participation. This article critically interrogates inclusive educational practices capable of cultivating transformative and holistic learning environments within tertiary education. Drawing selectively upon Paulo Freire’s critical pedagogy and Kumaravadivelu’s post-method pedagogical orientation, the study argues that meaningful inclusion necessitates dialogic, context-sensitive, and socially emancipatory educational frameworks that challenge institutional inequities while validating learner agency and plurality. Particular attention is devoted to culturally responsive pedagogy, Universal Design for Learning (UDL), differentiated instruction, and Social Emotional Learning (SEL) as foundational paradigms for equitable educational transformation. The discussion further examines equity-oriented institutional policies, disability inclusion frameworks, trauma-informed educational systems, collaborative pedagogical ecosystems, inclusive curriculum design, and faculty professionalization initiatives. The article contends that inclusive tertiary education must transcend procedural compliance and instead pursue systemic restructuring grounded in equity, accessibility, democratic participation, representation, critical consciousness, and belongingness. Ultimately, holistic education within higher education can only be meaningfully realized when universities cultivate culturally sustaining, emotionally affirming, technologically accessible, and socially just academic environments capable of fostering both intellectual empowerment and human emancipation.